2017
DOI: 10.18071/isz.70.0358
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral acute angle-closure glaucoma induced by duloxetine

Abstract: Introduction - To present a rare case of bilateral acute angle-closure glaucoma secondary to duloxetine administered for the treatment of depression. Case presentation - A 46 year old woman developed bilateral closed angle glaucoma after 15 days of duloxetine usage. Intraocular pressures (IOP) were 52 and 55 mm Hg in right and left eyes respectively, with shallow anterior chamber and angle closure on gonioscopy. Discontinuing duloxetine treatment, initiation of antiglaucomatous treatment and bilateral Nd:YAG L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…SSRI agents have been reported to increase the intraocular pressure in another review, but this did not require discontinuation of the drugs and only required follow-up by the Ophthalmology team [9]. However, some case reports have indicated that SNRIs such as Duloxetine [2,10] and Venlafaxine [11,12], and SSRIs such as sertraline [13], paroxetine [14], and citalopram [15] can cause angle-closure glaucoma. The reason is reported in these studies as the serotonin receptors in the iris, cornea, and ciliary body.…”
Section: Review Of the Baseline And 3rd Month Results Of The Patients...mentioning
confidence: 99%
See 1 more Smart Citation
“…SSRI agents have been reported to increase the intraocular pressure in another review, but this did not require discontinuation of the drugs and only required follow-up by the Ophthalmology team [9]. However, some case reports have indicated that SNRIs such as Duloxetine [2,10] and Venlafaxine [11,12], and SSRIs such as sertraline [13], paroxetine [14], and citalopram [15] can cause angle-closure glaucoma. The reason is reported in these studies as the serotonin receptors in the iris, cornea, and ciliary body.…”
Section: Review Of the Baseline And 3rd Month Results Of The Patients...mentioning
confidence: 99%
“…[1]. Some studies in the literature have reported that duloxetine [2,3] and Selective Serotonin Reuptake Inhibitors (SSRI) [4][5][6] may lead to angle-closure glaucoma. However, these have been in the form of case reports or case series.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the causative relationship might be overestimated, considering that psychiatric disorders could be secondary to the glaucoma diagnosis even secondary to the use of antiglaucoma medication. Secondly, some antidepressants such as topiramate ( Kocamaz and Karadag, 2019 ), aripiprazole ( Shen et al, 2018 ), milnacipran ( Keks et al, 2018 ), and duloxetine ( Mahmut et al, 2017 ) have potential eye side effects, such as acute onset angle-closure glaucoma. Chen et al (2016) found that patients using selective serotonin reuptake inhibitors (SSRIs) have a 5.80-fold increased risk of angle-closure glaucoma in a week.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of lowering IOP is good, but the incidence of postoperative complications is high (26). OCT can directly image the lens, the measured lens thickness, and the relative position of the lens more objectively (27).…”
Section: Discussionmentioning
confidence: 99%